Tourist Motivation and Viral Marketing as Determinants of Destination Interest: Evidence from Lambangan Pauno Beach - Mardiani, Mardiani; Wolok, Tineke (Pascasarjana STIE Amkop Makassar, 2025)
This study aims to analyse the effect of viral marketing and tourist motivation on visiting interest, both partially and simultaneously. Conducted at Lambangan Pauno Beach in Banggai Laut Regency, the research adopts a quantitative approach with data collected through questionnaires. A total of 150 respondents were selected using the Cochran formula, and the data were analysed using multiple linear regression. The results show that viral marketing does not have a significant partial effect on visiting interest (sig. 0.412 > 0.05), while tourist motivation has a positive and significant influence (sig. 0.000 < 0.05). However, when examined simultaneously, both viral marketing and tourist motivation significantly affect visiting interest (sig. 0.000 < 0.05), with tourist motivation emerging as the more dominant factor. The study concludes that tourists’ motivation is the primary driver behind interest in visiting Lambangan Pauno Beach, whereas viral marketing alone does not significantly influence visitation interest. The research is limited in scope, focusing only on viral marketing and tourist motivation without considering other potential influencing factors such as service quality, accessibility, or available facilities. Nonetheless, the findings offer valuable insights for tourism managers, marketers, and local government agencies by highlighting the importance of enhancing tourist motivation to increase visitation interest. Furthermore, this study contributes to the broader fields of tourism market. Kata Kunci: Viral Marketing, Tourist Motivation, Interest in Visiting